Ethics and health care : an introduction - Moskop, John C. (Cambridge applied ethics, 2016)
"This book provides a concise introduction to the major concepts, principles, and issues in health care ethics, using case studies throughout to illustrate and analyse challenging ethical issues in contemporary health care. Topics range widely, from confidentiality and truthfulness to end-of-life care and research on human subjects. Ethics and Health Care will be a vital resource for students of applied ethics, bioethics, professional ethics, health law, and medical sociology, as well as students of medicine, nursing, and other health care professions"--